2000
DOI: 10.3354/dao039135
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies on optimal requirements for the growth of Spironucleus vortens, an intestinal parasite of the freshwater angelfish

Abstract: Spironucleus vortens were cultivated in either an artificial medium at different temperatures, or in medium at vanous pH conditions or supplemented with different bile concentrations at 25OC. Temperature, pH and bile requirements for the optimal growth of the parasite were determined. Parasites multiplied quickly at 28 and 31°C and reached maximum numbers on Day 4 of cultivation, whereafter they did not survive. At 25"C, parasites survived longer than those at 28 and 31°C with no difference in multiplication r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Intracellular protozoans such as Apicomplexa often require co-culture in cell lines (Tzipori 1998), and the complexity of the life histories of Metazoan parasites usually imposes limitations for in vitro cultivation approaches. Relatively few fish parasites can be cultured or maintained in vitro, and these are mainly protozoans: blood flagellates (Thomas & Woo 1992, Bienek & Belosevic 1997, Davies et al 1999, intestinal diplomonad flagellates (Buchmann & Uldal 1996, Sterud 1998, Sangmaneedet & Smith 2000, ectoparasitic dinoflagellates (Oestmann & Lewis 1996), histophagous ciliates (Crosbie & Munday 1999) and microsporidians (Wongtavatchai et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular protozoans such as Apicomplexa often require co-culture in cell lines (Tzipori 1998), and the complexity of the life histories of Metazoan parasites usually imposes limitations for in vitro cultivation approaches. Relatively few fish parasites can be cultured or maintained in vitro, and these are mainly protozoans: blood flagellates (Thomas & Woo 1992, Bienek & Belosevic 1997, Davies et al 1999, intestinal diplomonad flagellates (Buchmann & Uldal 1996, Sterud 1998, Sangmaneedet & Smith 2000, ectoparasitic dinoflagellates (Oestmann & Lewis 1996), histophagous ciliates (Crosbie & Munday 1999) and microsporidians (Wongtavatchai et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The disparity in temperatures between the two environments is of particular interest. Sang‐maneedet and Smith (2000) showed that S. vortens can live and reproduce at temperatures from 22–34°C. Our present results have shown that this flagellate can also be successfully cultivated at 5°C and 15°C.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, approximately three cm of the anterior‐middle section was cut free with sterile scissors and put into a 15 × 100‐mm plastic screw‐capped tube containing 10 ml of Keister's medium (bile‐supplemented TYI‐S‐33 medium) to which was added 100 μg ml −1 gentamicin and 150 μg ml −1 ampicillin. Keister's medium has previously been used for the successful cultivation of a number of diplomonad species (Keister 1983; Poynton et al 1995; Sangmaneedet and Smith 2000; Sterud 1998a; Sterud, Mo, and Poppe 1997). The tube was shaken to wash out flagellates from the mucosa.…”
Section: Methodsmentioning
confidence: 99%
“…The diplomonad Spironucleus vortens is a small, protozoan flagellate, which is the suspected agent of hole‐in‐the‐head disease in cichlids (Paull & Matthews 2001). Spironucleus vortens is related to the ubiquitous diplomonad human parasite Giardia intestinalis and was shown to generate high cell numbers, while sustaining a broad range of temperatures and pHs in vivo (Sangmaneedet & Smith 2000). It is therefore an excellent candidate for investigating diplomonad biology.…”
mentioning
confidence: 99%